The effect of changing the moisture levels of dry extruded and wet canned diets on physical activity in cats. (17th April 2017) - Thomas, D. G.; Post, M.; Bosch, G.
Abstract: Obesity levels in cats are increasing and the main causative factor is higher energy intake v . energy expenditure over time. Therefore, altering energy expenditure by enhancing physical activity of the cat could be a strategy to reduce obesity. Hydrating commercial dry diets with water increased activity in cats; however, no study has compared this approach with feeding high-moisture canned diets. Eight healthy male neutered domestic shorthair cats were fed four different dietary treatments in a Latin square design. Treatments were a canned diet 'as is' (82 % moisture) and freeze-dried (4 %), a dry diet 'as is' (3 %) and with added water (70 %). Cat activity was measured continuously using Actical ® accelerometers. Cats were group housed during the first 14 d of each period and then moved to individual cages for 7 d with faecal and urine production measured over the final 4 d. Intake was similar for each diet. The average activity over 24 h was not different between treatments ( P > 0·05). However, the ratio between average activity during the day v . at night was higher when cats were fed the dry diet ( P = 0·030). Total water intake and urine volume increased when the canned diet was fed ( P < 0·001). The similarity in total activity of the cats on the treatments indicates that dietary moisture or diet type did not have a major effect on these cats. However, the stronger diurnal activity patterns observed in the cats when they were fed the dry diet are intriguing and require further study.